Campaign for Determining the Longitude of the Fundamental Point of the Astronomic Observatory in Naples — III. The Equation for Longitude - Fichera, E. (The International Hydrographic Review, 2015)
In this article we shall be dealing in more detail with the equation used for determining the longitude of the fundamental point of the Capodimonte Astronomic Observatory, Naples. We shall analyse certain problems well known to specialists but which are not easily found in geodetic astronomy literature. Several new developments never before used in determinations of this kind and that we have deduced during the course of our observations will also be given.